IoT on power monitoring and protection for home energy consumption - Artono, Budi; Putra, Rakhmad Gusta; Prasetyo, Yuli; Ningrum, Hanifah Nur Kumala (Geuthèë Institute, 2025)
Electrical hazards can occur due to inadequate protection systems, often leading to fires in homes or buildings. One major cause of this issue is users' lack of knowledge regarding standard electrical installations. To overcome this, the Internet of Things (IoT) offers a promising solution by enabling remote and real-time control and monitoring of electrical devices. By integrating IoT technology with home electrical systems, users can enhance safety and manage energy consumption more effectively. A practical implementation involves using a digital kWh meter, which allows accurate measurement of electrical quantities such as current, voltage, power, and power factor (cos Φ) without requiring additional sensors. The system was tested using three household loads: a 5W smartphone charger, a 40W lamp, and a 100W single-phase motor. Monitoring is done through an Android application and a web browser interface, making it accessible and user-friendly. These platforms display real-time electrical parameters and provide estimates of energy costs. Additionally, the system includes a current limitation feature, which is configured by Arduino and can be adjusted through the Android or web interface. This adds an extra layer of protection against overloads, enhancing the safety and efficiency of household electrical usage. The integration of IoT and digital metering contributes significantly to smarter and safer energy management.